Poverty Reduction and Growth Trust : 2017 Borrowing Agreements with the Bank of Italy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
On July 17, 2017, the Fund, as Trustee of the Poverty Reduction and Growth Trust (PRGT or Trust), entered into a new borrowing agreement (the 'Agreement') with the Bank of Italy (hereafter, Italy or Purchaser), by which Italy will provide new resources to the Extended Credit Facility Loan Account of the PRGT in the total amount of up to SDR 400 million.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Agreement; Better-Than-Expected Loan Mobilization Outcome; Loan Account; PP; SDR; Italy